2019
DOI: 10.1002/cbic.201900235
|View full text |Cite
|
Sign up to set email alerts
|

A Temperature‐Driven, Reversible, Helical‐Handedness Inversion in Peptaibol Analogues Tuned by the C‐Terminal Capping Moiety

Abstract: Trichogin is a natural peptide endowed with antimicrobial and antitumor activity. A member of the peptaibol family, trichogin possesses a C‐terminal amino alcohol. In the past, this moiety was substituted for a methyl ester for synthetic purposes and it was observed that this apparently slight modification caused significant changes in the peptide bioactivity. With the aim of understanding the reasons behind such observations, a detailed spectroscopic study on a number of trichogin analogues has been performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The spectral values are close to those of a monoradical species, but with a bit of extra line broadening (the peak-to-peak width of the central transition is 0.35 mT, while for mono-labeled trichogins, values of 0.26-0.33 mT were reported [44]). Previously, for Tri 1,8 in a polar solvent, we found the TOAC 1 -TOAC 8 distance to be above 1.5 nm [24]. Therefore, the broadening cannot be attributed to a through-space exchange coupling.…”
Section: Cw Epr Datamentioning
confidence: 72%
See 4 more Smart Citations
“…The spectral values are close to those of a monoradical species, but with a bit of extra line broadening (the peak-to-peak width of the central transition is 0.35 mT, while for mono-labeled trichogins, values of 0.26-0.33 mT were reported [44]). Previously, for Tri 1,8 in a polar solvent, we found the TOAC 1 -TOAC 8 distance to be above 1.5 nm [24]. Therefore, the broadening cannot be attributed to a through-space exchange coupling.…”
Section: Cw Epr Datamentioning
confidence: 72%
“…In the literature, on the basis of conformational studies (by circular dichroism, 2D-NMR, X-ray diffraction analysis), it was suggested that a pivotal role in analyte binding is played by the central, flexible -Gly 5 -Gly 6 -motif of trichogin [49], which may form a loop around the metal ion, combined with the relatively short length of trichogin (ca. 2.2 nm in a 3 10 -helix [24,44]). These features may provide either a structural match for the coordination shell of the metal ion or the right coordination number for specific ions.…”
Section: Toac Trichogin Ga IVmentioning
confidence: 98%
See 3 more Smart Citations